Correlation Between Immunohistochemical Expression of Epstein-Barr Virus Latent Membrane Protein-1 (LMP-1) and Clinical Stages of Sinonasal Carcinoma - Liza Retno Dewi; Muhammad Amsyar Akil; Eka Savitri; Abdul Punagi (Nusantara Medical Science Journal, 2022)
Introduction: Sinonasal tumors are rarely found. The protected nature of the sinuses makes early detection of tumors growing in these areas difficult. The Epstein-Barr virus is one of the most common viruses found in humans; which expresses Latent Membrane Protein-1 (LMP-1) that can transform cell lines and alter cell phenotype due to its oncogenic potential. Objective: To investigate the relationship between immunohistochemical expression of Latent Membrane Protein-1 (LMP-1) from Epstein-Barr virus and clinical stages of sinonasal carcinoma. Methods: This cross-sectional study was carried out in DR. Wahidin Sudirohusodo General Hospital and anatomic pathology of Hasanuddin University Hospital, Makassar, South Sulawesi, Indonesia, from October 2016 to March 2017. Histopathological samples from biopsy specimen of all subjects diagnosed with sinonasal carcinoma in Otorhinolaryngology-Head and Neck Surgery outpatient clinic were taken and examined for LMP-1 expression using immunohistochemical staining. The samples were taken from paraffin block from patients. Result: There were 33 males (67.3%) and 16 females (32.7%) with sinonasal carcinoma who participated in this study. The majority of participants aged ≥50 years (25 people, 51.0%) and worked as farmers (27 people, 55.1%). A significant correlation between LMP-1 expression and sinonasal carcinoma clinical stages was found (Spearman’s correlation r = 0.355 and p <0.001). Conclusion: Higher LMP-1 expression correlates with higher sinonasal carcinoma clinical stage in patients aged <50 years.